Inovasi Virtual Exhibition Masa Depan - Indira Khairunnisa; Adinda Dhiya Hasna; Heidy Bherti Kharoline; Any Ariani Noor (Altasia Jurnal Pariwisata Indonesia, 2021)
The MICE (Meeting, Incentive, Conference, and Exhibition) industry is part of the tourism sector that has suffered significant losses due to the Covid-19 outbreak. Seeing this, experts in the field of MICE are trying to create innovations that can sustain the MICE industry during a pandemic. One of them is using technology to creat applications in the form of a virtual exhibition. The development that continues to occur in the world of information technology is the reason for this research, with the aim of finding opportunities that can be a reference for MICE activity actors in innovation, as well as developing MICE activities, especially virtual exhibitions in the future with the Virtual Reality 360 technology. This study collects data in the form of research and literature references that support theories related to the problem that is the focus of this research. Based on the results of the analysis, it was found that virtual exhibitions are becoming a trend during the current pandemic. The virtual exhibition is then further developed into Three Dimensional (3D) technology. By utilizing technological developments, such as google cardboard, it can be a means of supporting the presence of an innovation at a virtual exhibition in the form of the implementation of 360 virtual reality technology. By obtaining this supporting tool, it is hoped that it can provide opportunities for experts in the MICE industry to further develop virtual exhibition applications. with the implementation of 360 virtual reality technology.